Circadian rhythm of serum cytidine deaminase in patients with rheumatoid arthritis during rest and exercise. Issue 6 (June 1989) - Thompson, P W; James, I T; Wheatcroft, S; Pownall, R; Barnes, C G
Abstract : Circadian rhythm of serum cytidine deaminase and C reactive protein was assessed in 11 inpatients with rheumatoid arthritis who were crossed between 24 hours of bed rest and 24 hours of normal ward activity. Blood was taken at six hourly intervals and the results analysed by fitting sine waves with an assumed period of 24 hours to the measured concentrations. Cytidine deaminase after activity, but not at rest, showed circadian variation, with a 24 hour mean level of 17.4 units (normal 3-13 units) and an amplitude of 1.1 units. The circadian variation, defined as the curve's peak to trough difference as a percentage of the 24 hour mean, was 12.3% and occurred at 1208 hours. C reactive protein showed no significant circadian rhythm, in keeping with published findings. The timing of the peak in serum cytidine deaminase concentrations after a period of morning physiotherapy, but not during the bedrest morning, suggests that exercise accounts for the circadian rhythm, probably by increasing the lymphatic clearance from inflamed joints.